Prayers of The Eucharist: Early and Reformed - Ronald Claud Dudley Jasper; G. J. Cuming (Minnesota The Liturgical Press, 1990)
texts translated and edited with commentary, R.C.D. Jasper and G.J. Cuming.
Third Edition, Revised and Enlarged
Keywords: Liturgy (3GddGghJ GdWbSj (B- (3GddjJhQLjGs; Eucharistic prayers -- Texts; Theology